Nursing students' role in the “O Brasil Conta Comigo” action to confront COVID-19 (Research, Society and Development, 2021)
Objective: to report the experience of nursing students working in the strategic action “O Brasil Conta Comigo” facing the COVID-19 pandemic. Method: this is a descriptive-reflective experience report, based on the experiences of nursing students in Family Health Units in the city of Curitiba-PR in the context of the strategic action, between July and December 2020. Results: the actions carried out in the health services and the managerial skills developed were described. It also reflected on the particularities of the action proposed by the federal government to control the pandemic and its impacts on students, teachers and health services. Conclusion: the performance of students enabled the development of managerial and care skills, highlighted the need for professional development and improvement of work processes in primary care, as well as having the potential to incite discussion on the subject among educational institutions.